2021
DOI: 10.1007/s11069-020-04462-2
|View full text |Cite
|
Sign up to set email alerts
|

Extreme sea levels at Rapa Nui (Easter Island) during intense atmospheric rivers

Abstract: In addition to the tsunami hazard posed by distant great earthquakes, Rapa Nui (Easter Island), in the Southeast Pacific Ocean, is exposed to frequent and intense coastal storms. Here, we use sea-level records and field surveys guided by video and photographic footage to show that extreme sea levels at Rapa Nui occur much more frequent than previously thought and thus constitute an unrecognized hazard to the inland's maritime supply chain. We found that extreme sea-level events, including the two most extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Links should be established between ARs and sea‐level extremes on a more global basis (cf. Carvajal et al., 2021; Ridder et al., 2018). We used the AR catalog of Gershunov et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Links should be established between ARs and sea‐level extremes on a more global basis (cf. Carvajal et al., 2021; Ridder et al., 2018). We used the AR catalog of Gershunov et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The last decade studies have shown that Rapa Nui people have developed advanced eco-friendly gardens in the central parts of the island (Hunt & Lipo, 2012, Lima et al, 2020. There are indications that a giant tsunami wave (Pollard et al) or extreme rains caused by so-called atmospheric rivers could sweep the Rapa Nui (Carvaja et al, 2021) and destroy food resources. The importance of the above factors can be significant and complicate the picture of Rapa Nui population changes.…”
Section: Population Evolution : Microbiology Parallel and The Rapa Nu...mentioning
confidence: 99%
“…6, we see that the key Cluster 4 events can actually be caused by a wide variety of synoptic phenomena. We first look at the correspondence between these events and atmospheric rivers, which are known to sometimes cause extreme sea level rise on Rapa Nui (Carvajal et al 2021). We use the atmospheric river algorithm tested in Reid et al (2020) to calculate all atmospheric rivers in the Southern Hemisphere in ERA5 for the period of our analyses .…”
Section: Caption)mentioning
confidence: 99%